Refraction of Alms in Forming Empathetic Character in Early Childhood in RA Raudhatul Jannah (Current Research in Education: Conference Series Journal, 2024)
This research aims to describe the application of habituation methods and teachers' efforts to foster empathy in young children through the Almsgiving Friday Alms program at Ra Raudhatul Jannah, Purwakarta City. This research uses a qualitative descriptive approach, with the results showing that the habit of Alms Friday Blessings can foster an attitude of empathy in children, so that schools can sustainably implement this activity. So, based on the results of the research conducted, it can be concluded that the teacher's efforts to foster an empathetic attitude in children at RA Raudhatul Jannah, Purwakarta City through the habituation method and the teacher's efforts to increase the empathetic attitude in children carried out by directly involving children in the Alms Friday Blessings activity succeeded in changing the child's mindset from not caring to caring.